The detrital record of late‐Miocene to Pliocene surface uplift and exhumation of the Venezuelan Andes in the Maracaibo and Barinas foreland basins. (5th October 2015) - Bermúdez, M. A.; Hoorn, C.; Bernet, M.; Carrillo, E.; van der Beek, P. A.; Garver, J. I.; Mora, J. L.; Mehrkian, K.
Abstract: A multidisciplinary approach, combining sediment petrographic, palynological and thermochronological techniques, has been used to study the Miocene‐Pliocene sedimentary record of the evolution of the Venezuelan Andes. Samples from the Maracaibo (pro‐wedge) and Barinas (retro‐wedge) foreland basins, proximal to this doubly vergent mountain belt, indicate that fluvial and alluvial‐fan sediments of similar composition were shed to both sides of the Venezuelan Andes. Granitic and gneissic detritus was derived from the core of the mountain belt, whereas sedimentary cover rocks and uplifted foreland basin sediments were recycled from its flanks. Palynological evidence from the Maracaibo and Barinas basins constrains depositional ages of the studied sections from late Miocene to Pliocene. The pollen assemblages from the Maracaibo Basin are indicative of mountain vegetation, implying surface elevations of up to 3500–4000 m in the Venezuelan Andes at this time. Detrital apatite fission‐track (AFT) data were obtained from both stratigraphic sections. In samples from the Maracaibo basin, the youngest AFT grain‐age population has relatively static minimum ages of 5 ± 2 Ma, whereas for the Barinas basin samples AFT minimum ages are 7 ± 2 Ma. With exception of two samples collected from the Eocene Pagüey Formation and from the very base of the Miocene Parángula Formation, no evidence for resetting and track annealing in apatite due to burial heating in the basins was found. This is supported by rock‐eval analyses on organic matter and thermal modelling results. Therefore, for all other samples the detrital AFT ages reflect source area cooling and impose minimum age constraints on sediment deposition. The main phase of surface uplift, topography and relief generation, and erosional exhumation in the Venezuelan Andes occurred during the late Miocene to Pliocene. The Neogene evolution of the Venezuelan Andes bears certain similarities with the evolution of the Eastern Cordillera in Colombia, although they are not driven by exactly the same underlying geodynamic processes. The progressive development of the two mountain belts is seen in the context of collision of the Panama arc with northwestern South America and the closure of the Panama seaway in Miocene times, as well as contemporaneous movement of the Caribbean plate to the east and clock‐wise rotation of the Maracaibo block.